1994
DOI: 10.1007/bf00873964
|View full text |Cite
|
Sign up to set email alerts
|

Vinorelbine in pre-treated advanced head & neck squamous cell carcinoma

Abstract: VNB, in this series of heavily pre-treated patients with head & neck cancer, did not reveal an antitumor activity of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…These studies indicated vinorelbine as eVective in vitro, and an additive eVect of combining vinorelbine and irradiation could be demonstrated. In phase II studies vinorelbine has proved to be a potential and active drug against advanced HNSCC (Degardin et al 1998;Testolin et al 1994). Vinorelbine combined with cisplatin alone or with cisplatin and 5-FU followed by hyperfractionated irradiation has shown encouraging results in the treatment of advanced HNSCC (Espinosa et al 2002;Orecchia et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicated vinorelbine as eVective in vitro, and an additive eVect of combining vinorelbine and irradiation could be demonstrated. In phase II studies vinorelbine has proved to be a potential and active drug against advanced HNSCC (Degardin et al 1998;Testolin et al 1994). Vinorelbine combined with cisplatin alone or with cisplatin and 5-FU followed by hyperfractionated irradiation has shown encouraging results in the treatment of advanced HNSCC (Espinosa et al 2002;Orecchia et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic eVect of vinorelbine has been demonstrated against lung, breast and ovarian cancers (Canobbio et al 1989;George et al 1989;DePierre et al 1991). In the preclinical studies as well as in the phase I-II studies it has shown eYcacy to HNSCC (Erjala et al 2002;Degardin et al 1998;Testolin et al 1994). At present, vinorelbine is in routine clinical use in breast and lung cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of previous phase I/II studies, which found VNR to be an active and tolerable drug in squamous cell carcinoma of the lung [6,7], esophagus [10] and head and neck [8,9,11] when combined with cisplatinum, we initiated a phase II trial to assess the tolerance and activity of VNR in combination with the platinum analogue carboplatin in recurrent HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…For pain control metamizol, diclofenac and tramadol were administered and the VNR infusion was interrupted. As previously described [11], and defined by the criteria for study entry, all patients had normal neurologic conditions prior to therapy. None of the 24 patients experienced other treatment-related neurological toxicity, except 6 patients, who had constipation.…”
Section: Response To Therapymentioning
confidence: 99%
“…Das Ansprechen bestand aus einer parziellen Remission bei einem Patienten (6 %). Bei 4 Patienten kam es zu einem vorüberge-henden Wachstumsstillstand [7]. In den beiden anderen Studien mit zusammen 96 Patienten wurden neben vorbehandelten Patienten auch unvorbehandelte Patienten eingeschlossen.…”
Section: Gemcitabin Und Vinorelbinunclassified